Implementation of School Literacy Movement of The Class XI SMK Kesehatan Haji Sumatera Utara - Chairunnissa, Nazli Fahada (Education Achievement: Journal of Science and Research, 2023)
The purpose of this research was to know the students’ implementation of school literacy program. The design of this research was descriptive quantitative research by using Survey method. The instrument of this research was questionnaire to know the implementation of students toward the school literacy program. The population of this research was all of the eleventh grade students of SMK Kesehatan Haji Sumut which consisted of 3 majors and 59 students. The sample was all of the population because this research was using total sampling technique The instrument validity test was carried out by using expert validity to three experts as instrument validators and to analyze the data was done by identifying the responses, counting the percentages of each indicator and taking the conclusion. The results of the research showed that the average score of the habituation stage of school literacy program was 38,07% which was good perception. The average score of the development stage of school literacy program was 38,22% which was good perception. The last, the average score of the learning stage of school literacy program was 38,66% which was good perception. It can be concluded, the average mean of students’ perception toward the implementation of school literacy program was 38,30% which was in good category in the rating interpretation 60%-39,99%.